Acceleration of Fracture Healing by Overexpression of Basic Fibroblast Growth Factor in the Mesenchymal Stromal Cells. (9th August 2017) - Zhang, Hongliang; Kot, Alexander; Lay, Yu-An E.; Fierro, Fernando A.; Chen, Haiyan; Lane, Nancy E.; Yao, Wei
Abstract: In this study, we engineered mesenchymal stem cells (MSCs) to over-express basic fibroblast growth factor (bFGF) and evaluated its effects on fracture healing. Adipose-derived mouse MSCs were transduced to express bFGF and green fluorescence protein (ADSC bFGF -GFP). Closed-femoral fractures were performed with osterix-mCherry reporter mice of both sexes. The mice received 3 × 10 5 ADSCs transfected with control vector or bFGF via intramuscular injection within or around the fracture sites. Mice were euthanized at days 7, 14, and 35 to monitor MSC engraftment, osteogenic differentiation, callus formation, and bone strength. Compared to ADSC culture alone, ADSC bFGF increased bFGF expression and higher levels of bFGF and vascular endothelial growth factor (VEGF) in the culture supernatant for up to 14 days. ADSC bFGF treatment increased GFP-labeled MSCs at the fracture gaps and these cells were incorporated into the newly formed callus. quantitative reverse transcription polymerase chain reaction (qRT-PCR) from the callus revealed a 2- to 12-fold increase in the expression of genes associated with nervous system regeneration, angiogenesis, and matrix formation. Compared to the control, ADSC bFGF treatment increased VEGF expression at the periosteal region of the callus, remodeling of collagen into mineralized callus and bone strength. In summary, MSC bFGF accelerated fracture healing by increasing the production of growth factors that stimulated angiogenesis and differentiation of MSCs to osteoblasts that formed new bone and accelerated fracture repair. This novel treatment may reduce the time required for fracture healing. Abstract : Multiple Beneficial Effects for ADSC bFGF in Fracture Repair ADSC bFGF directly migrated to facture sites and acted as cell supplement and replacement. ADSC bFGF delivered trophic factors mechanism such as bFGF, VEGF, and PDGF via paracrine that stimulated angiogenesis, osteoblast differentiation, and bone formation at the fracture site ADSC bFGF induced a rapid cartilage turnover through endochondral ossification and enhances bone strength. Taken together, MSC bFGF accelerated fracture healing by increasing the production of growth factors that stimulated angiogenesis and differentiation of MSCs to osteoblasts that formed new bone and accelerated fracture repair.